Comparable Outcomes and Health-Related Quality of Life for Severe Aplastic Anemia: Haploidentical Combined With a Single Cord Blood Unit vs Matched Related Transplants - Lei, Meiqing; Li, Xiaoli; Zhang, Yanming; Qu, Qi; Jiao, Wenjing; Zhou, Huifen; Wang, Qingyuan; Qiu, Huiying; Tang, Xiaowen; Han, Yue; Fu, Chengcheng; Jin, Zhengming; et al. (Frontiers in Oncology, 2022)
We retrospectively compared the outcomes and health-related quality of life (HRQoL) of severe aplastic anemia (SAA) patients who received haploidentical hematopoietic stem cell transplantation with a single unrelated cord blood unit (Haplo-cord HSCT) (n = 180) or matched related donor (MRD)-HSCT (n = 128). After propensity score matching, we were able to match 88 patients in each group and to compare the outcomes between the two matched-pair groups. Haplo-cord recipients exhibited a longer median days for neutrophil engraftment (12 vs 11, P = 0.001) and for platelet engraftment (15 vs 13, P = 0.003). Haplo-cord recipients a high cumulative incidence of grades II–IV acute graft-versus-host disease (GVHD) (29.8 vs 14.0%, P = 0.006), while similar III–IV acute GVHD, total chronic GVHD, and moderate to severe chronic GVHD at 4 year (all P < 0.05). Among the Haplo-cord HSCT and MRD-HSCT groups, the four-year GVHD-free/failure-free survival rates were 73.5% and 66.9% (P = 0.388) respectively, and the overall survival rates were 81.5% and 77.2% (P = 0.484), respectively. Similar comparable results also were observed between the corresponding first-line, older or younger than 40 years old subgroups. The Haplo-cord HSCT group exhibited higher scores in the physical component summary, physical functioning, general health and social functioning than the MRD-HSCT group (all P < 0.05). In the multivariate analysis, young age and Haplo-cord HSCT were favorable factors for HRQoL, while moderate to severe cGVHD was associated with lower HRQoL. These results suggest that for SAA patients, Haplo-cord HSCT could achieve at least comparable efficacy and HRQoL to MRD-HSCT.